Cost Estimation On The Development Of Multifunctional Drinking Bottle Products (Tissue Storage) Using Full Costing Method - Rossi Septy Wahyuni; Yuni Sulistyowati; Mei Raharja (Journal of Information System, Informatics and Computing, 2022)
The development of multifunctional drinking bottles as well as tissue storage is one of the needs and desires of customers. This product requires further analysis of what costs are used through the calculation of cost estimates. The system development in this study applies the full costing method. The use of this full costing method works by calculating the overall cost of product development through the calculation of the cost of production, selling price and break-even point obtained from collecting data on labor costs, raw materials, factory overhead, production quantities and selling prices. The results of this study obtained the total cost of raw materials for a period of 1 month with a total of Rp. 243.250.000,-, the cost of production with the amount of Rp. 260,462,247,-, the selling price per unit is Rp. 104,184.90, - with a profit of 30%, namely Rp. 78,138,674 and the break-even point of Rp. 372.626.70,- and 1904 units of multifunctional drinking bottle products as well as tissue storage.